Barney's horse : story and pictures - Hoff, Syd, 1912- (New York : Harper & Row, 1987)
Though he is used to the city streets, Barney's horse becomes frightened of the noisy new overhead trains.
Booklist
3.0
K-3
Keywords: Horses -- Fiction; City and town life -- Fiction; Horses -- Fiction; City life -- Fiction